QUALITATIVE ASSESSMENT OF SOIL IN SELECTED RURAL AND URBAN AREAS: A PHYSICAL TEST TO THE VIABILITY OF URBAN GARDENING - Agero, Alma D; Torres, Marry Ann B; Celestial, Virgie Marie P (Journal of Agriculture and Technology Management, 2022)
The study analyzes the soil characteristics in rural and urban areas in Lapu-Lapu City, Cebu; Valencia, Negros Oriental; and La Carlota City, Negros Occidental. It attempts to relate the soil's physical properties to the natural and human processes occurring in the area and the viability of urban gardening. Soil samples were taken from the identified sites and tested with the following physical tests: texture test by felt finger and hydrometer method, and pH test. The soil samples under study were classified as loam, varying only in silt, sand, and loam. The pH of soils varies from slightly acidic to moderately alkaline, ranging from 5.20 to 8.37. Considering the viability for urban gardening, the results revealed that the sample site as residential in Lapulapu City is feasible for a household gardening with the soil type of loamy and pH of 7.98.